Changes in nutritive quality of Pennisetum purpureum var. Red Napier with maturity - Nik Hassan, Nik Zuraila (2015)
The nutritive quality of pasture is important in order to satisfy the nutrient requirements of animals fed on the pasture. The study was conducted to evaluate changes in nutritive quality of Red Napier with maturity. The nutritive quality measurement included Crude Protein (CP), Neutral Detergent Fibre (NDF), Acid Detergent Fibre (ADF) and the morphological measurement included plant height (PH), moisture content (MC), number of tillers (NOT), Leaf to Stem Ratio (LSR) and dry matter yield (DMY). This experiment used the Randomized Complete Block Design (RCBD) with four replications. The treatments were 3, 5 and 7 weeks harvest intervals. Harvest intervals of 3 week gave the highest CP and cumulative dry matter yield (DMY) compared to harvest intervals at 5 week and 7 week. The 3 week cutting interval gave the lowest NDF and ADF. Cutting at 7 week interval gave the lowest dry matter yield. The harvest interval recommended for Red Napier is 3 week because grass cut at this interval had high nutritive quality as well as high dry matter yield. Another objective of the study was to evaluate whether Near Infrared Spectroscopy (NIRS) can be used to estimate nutritive quality of pastures. The analysis of of CP, NDF and ADF was conducted using conventional laboratory methods and the results were compared with that obtained using NIRS. It was found that there was no correlation between the results obtained from the two methods and the NIRS was not a reliable method to be used in this study. The inability to use NIRS in this experiment was due to improper calibration where samples of forage from a previous study were used to calibrate the equipment. The calibration with current sample was not done due to some error in the software. To get accurate result, a new calibration should be done with the current samples. This indicates the importance of using the correct samples for calibration if NIRS is to be effectively used.